Exploring Interactions Between Arkansas Urban Producers: Social Networks and Modes of Information Seeking - Catherine E. Sanders; Don W. Edgar; Casandra K. Cox; Leslie D. Edgar (Journal of Human Sciences and Extension, 2022)
The purpose of this study was to explore the social networks and interactions between urban producers in Arkansas through a social network analysis. Using a mixed-methods approach, the current study collected data about participants’ social network interactions and methods of seeking information for urban farming. Results indicated how and where participants preferred to obtain information, peer-to-peer interactions within the network, and key players or opinion leaders in the network. The methods used in the current study may serve as an example of social network articulation for populations without a formal network to assist with outreach to communities potentially underserved by Extension.